Effect of patient counseling on quality of life of hemodialysis patients in India - Thomas D; Joseph J; Francis B; Mohanta GP (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
End stage renal disease (ESRD) is a growing problem. The effect of patient counseling is to be defined on health-related quality of life. Objective: The purpose of this study was to find out the impact of patient counseling in health related quality of life (QoL). Methods: In this prospective interventional study, the Karnofsky Performance Status (KPS) for QoL questionnaire was used in test and control groups for data collection. The same data collection method was used during six months to study the effect of patient counseling. Results: Health related quality of life in test group showed a consistent improvement of 2% in six months. Improvement of awareness by patient counseling was also improved. Conclusion: As part of medication therapy management (MTM), patient counseling focusing on dialysis compliance, diet and medications are an effective way to improve health-related QoL and awareness in ESRD. Such services should be made mandatory by law in India to improve outcomes in chronic illness.